Obelia racemosa Fraser 1941 ... - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
? Obelia racemosa Fraser, 1941b ? Obelia racemosa Fraser, 1941b: 82, pl. 15, fig. 7. Holotype: USNM 4883: Canada, Nova Scotia, Western Bank, 91–119 m, 0 7 June 1880, schooner Mist, one colony, 25 cm high (Fraser 1941b), in poor condition, gonophores not seen, labelled “ syntype ”; ethanol. Type locality. Canada, Nova Scotia: Western Bank off Cape Breton Island, 50–65 fm (91–119 m) (Fraser 1941b). Current status. Species inquirenda. Remarks. In being designated as the “ type ”, material of Obelia racemosa at the NMNH (USNM 4883) was fixed as the name-bearing type of the species by Fraser (1941b). Although listed as a syntype in the online database, the specimen count is given as “1.” Fraser’s (1941b) original account of the species implies that it was based on a single specimen, as his description began with the words “Colony large….” The type examined here, consisting of one colony and a few fragments of it, is considered the holotype. Obelia racemosa has not been reported again. The holotype specimen is in ... : Published as part of Calder, Dale R. & Choong, Henry H. C., 2018, Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions, pp. 1-83 in Zootaxa 4487 (1) on page 71, DOI: 10.11646/zootaxa.4487.1.1, http://zenodo.org/record/1456161 ...